NARRATING THE SEX TRADE - WILSON, TRACIE L. ([S.l.])
1 online resource
Keywords: Examining a range of sex trade accounts from state documents, activist groups, folk narratives, and key figures in Polish, Ukrainian, and Yiddish literature, this book applies new materialist perspectives to cultural history, coloniality, and imperiality in the study of Europe's eastern borderlands.The text centers on late nineteenth- and early twentieth-century contexts, with eastern Galicia and Lviv as its focal point. However, these narratives flow across time and space, stretching back to the early modern period and continuing to the present across cities in the Americas, in Asia, and along the Mediterranean Sea. The book addresses the convergence of sex trade stories with older narratives, including links to early modern abduction accounts and antisemitic tropes. It also examines the involvement of prominent activists whose personal lives contributed to modern research in psychology and sexuality such as Bertha Pappenheim ("Anna O.") and Karl M. Baer. Its groundbreaking approach, unsettling notions of center and periphery, is relevant to study of a myriad of geographic contexts worldwide and to both historical analysis and present-day situations.This volume is intended for undergraduates, postgraduates, specialists, and general readers interested in east-central Europe, gender, coloniality/imperiality, migration, technology and modernity, narrative and literary studies, and new materialist approaches.